Oxidative stress triggers neuronal caspase-independent death: Endonuclease G involvement in programmed cell death-type III - Higgins, Gavin C; Beart, Philip M; Nagley, Phillip (Cellular and molecular life sciences : CMLS, 2009)
To characterize neuronal death, primary cortical neurons (C57/Black 6 J mice) were exposed to hydrogen peroxide (H₂O₂) and staurosporine. Both caused cell shrinkage, nuclear condensation, DNA fragmentation and loss of plasma membrane integrity. Neither treatment induced caspase-7 activity, but caspase-3 was activated by staurosporine but not H₂O₂. Each treatment caused redistribution from mitochondria of both endonuclease G (Endo G) and cytochrome c. Neurons knocked down for Endo G expression using siRNA showed reduction in both nuclear condensation and DNA fragmentation after treatment with H₂O₂, but not staurosporine. Endo G suppression protected cells against H₂O₂-induced cell death, while staurosporine-induced death was merely delayed. We conclude that staurosporine induces apoptosis in these neurons, but severe oxidative stress leads to Endo G-dependent death, in the absence of caspase activation (programmed cell death-type III). Therefore, oxidative stress triggers in neurons a form of necrosis that is a systematic cellular response subject to molecular regulation.